Comparative transcriptome analysis of wheat in response to corn leaf aphid, Rhopalosiphum maidis F. infestation - Jasrotia, Poonam; Sharma, Samriti; Nagpal, Mohini; Kamboj, Disha; Kashyap, Prem Lal; Kumar, Satish; Mishra, Chandra Nath; Kumar, Sudheer; Singh, Gyanendra Pratap (Frontiers in Plant Science, 2022)
Aphids are one of the most important insect pests of wheat crop in all wheat growing regions of the world. Amongst various aphid species, the corn leaf aphid (Rhopalosiphum maidis F.) is considered one of the most destructive insect pests of wheat in the North Western Plains region of India. Transcriptome profiling of highly susceptible wheat Triticum durum genotype, A-9-30-1 and tolerant wheat Triticum aestivum genotype, HD2967 was performed to investigate aphid-host interactions. The results obtained from differential gene expression analysis of R. maidis on the highly susceptible genotype, A-9-30-1 plants, when compared with the tolerant genotype, HD2967, showed that 212 genes were significantly upregulated and 1009 genes were significantly downregulated. Our findings demonstrated that the genes associated with defense were significantly higher in response to R. maidis on HD2967 as compared to A-9-30-1. Additionally, various genes with physiological attributes were expressed during aphid attack. Based on gene ontology classification, three classifications, such as, cellular components (CC), molecular function (MF), and biological processes (BP) of sequences were identified. KEGG enrichment analysis revealed that twenty-five pathway genes were differentially expressed during the infestation of wheat with R. maidis. Notable changes were observed in A-9-30-1 and HD2967 transcriptomic profiling after infestation. The results obtained in the present study will help to elucidate the mechanism governing host-pest interaction and may lead to the development of new methods for increasing the resistance level of wheat against R. maidis, including over-expression of defense-related genes.